Fissure tongue condition in a patient with down syndrome: A case report - Tanumiharja, Leonardo Jaya Setiadi; Azizah, Anna Nur; Tampubolon, Edria Benita; Patoni, Patoni; Tanumiharja, Marvin Jaya Setiadi (Science Midwifery, 2026)
Fissured tongue is a normal variation of the tongue in which the surface of the dorsum of the tongue has fissures, with varying depths. This condition is commonly found in patients with Down's syndrome. The patient comes with complaints of increasing tongue sensitivity to spicy and sour tastes. In general, patients do not feel any complaints or pain if the fissures are not too deep but there is a risk of food ingesting in these cracks. Fissured tongue will become a pathological condition if the depth reaches >5mm, causing the patient to seek treatment. The purpose of this case report is to provide an overview of patients who have Down's syndrome accompanied by fissured tongue. The patient in this case report was not given any medication and was only given oral health education and oral hygiene instructions both directly and to the patient's guardian.